Molecular Machinery and Pathophysiology of Mitochondrial Dynamics - Chiu, Yi-Han; Lin, Shu-Chuan Amy; Kuo, Chen-Hsin; Li, Chia-Jung (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria are double-membraned organelles that exhibit fluidity. They are the main site of cellular aerobic respiration, providing energy for cell proliferation, migration, and survival; hence, they are called “powerhouses.” Mitochondria play an important role in biological processes such as cell death, cell senescence, autophagy, lipid synthesis, calcium homeostasis, and iron balance. Fission and fusion are active processes that require many specialized proteins, including mechanical enzymes that physically alter mitochondrial membranes, and interface proteins that regulate the interaction of these mechanical proteins with organelles. This review discusses the molecular mechanisms of mitochondrial fusion, fission, and physiopathology, emphasizing the biological significance of mitochondrial morphology and dynamics. In particular, the regulatory mechanisms of mitochondria-related genes and proteins in animal cells are discussed, as well as research trends in mitochondrial dynamics, providing a theoretical reference for future mitochondrial research.